Pengaruh Financial Distress dan Profitabilitas Terhadap Opini Going Concern dengan Opini Shopping sebagai Variabel Pemoderasi - Parameswari, Anggraeni Eka; Prihatni, Rida; Nasution, Hafifah (LPPM Universitas Negeri Jakarta, 2023)
The purpose of this research is to determine the effect of financial distress and profitability on going concern opinion with opinion shopping as a moderating variable. This research used purposive sampling method as a sampling technique with 42 selected companies from the properties & real estate sector listed on the Indonesia Stock Exchange for the 2018-2020 period. This research uses secondary data obtained using documentation techniques from annual reports and financial reports. The data is analyzed using logistic regression analysis techniques using SPSS software. The results of this research showed that financial distress has no effect on going concern audit opinion while profitability has an effect. In addition, this research also showed that opinion shopping is unable to moderate the effects of these two variables on going concern opinion.